Lawness - Frederick Schauer (Washington University Law Review, 2018)
One of the more important insights in H.L.A.Hart’s The Concept of Law comes on the very first pages of the book, where Hart insightfully observes that the typical appeal for a definition of “law” is not really a search for a definition at all, but is instead a mask for any of a number of somewhat different and less definitional questions. We are puzzled about some aspect of law, Hart maintains, such as the relationship between law and morality, or the role of rules in a legal system, or the function of force and coercion in the legal order, but we disguise our specific puzzlements in a quest for a definition. Hart’s admonition about how to understand a request for a definition is sound advice, and it is no less sound because Hart himself turned out in the later chapters of his book to be unfaithful to his initial diagnosis and recommendation. Despite his claims in the first chapter that law might not be susceptible to traditional definition by necessary and sufficient conditions, despite the just-noted view that a request for a definition of law is typically a way of asking a different and more specific question about the character or operation of law, and despite his early explicit denial of the goal of seeking to define law at all, Hart proceeds in much of the balance of his book to offer what looks very much like a definition of law. In particular, he comes close to defining law as the union of primary and secondary rules when combined with the internalization of the ultimate rule of recognition by officials. And although Hart never says precisely that this is a definition of law, many of his followers, critics, and commentators have taken it to be precisely that. Brian Tamanaha, in his provocative and important challenge to many of the central themes of contemporary English-language analytical jurisprudence, especially contemporary analytical jurisprudence from a legal positivist perspective, does not appear to make Hart’s mistake. In saying that ”[l]aw . . . is whatever social groups conventionally attach the label ‘law’ to,” Tamanaha avoids giving us an actual definition of law, and thus distances himself from the many contemporary and not-so-contemporary efforts to specify the necessary, essential, or sufficient conditions for some social phenomenon being law. And although Tamanaha recognizes, along with Joseph Raz, that different cultures may have different concepts of law, or that one culture’s concept of law may change over time, Tamanaha insists that even within our concept of law the diversity of phenomena that are labeled or understood as law over time and across cultures is simply too wide to make any attempt at generalization either fruitful or illuminating. Tamanaha’s anti-essentialist project is an important voice in modern arguments about the nature of law. Along with various others who identify themselves as legal pluralists, Tamanaha is struck far more with the vast and seemingly foundational differences among so-called legal phenomena than with what, if anything, they may have in common. But in pursuing this agenda, and especially in purporting to offer a theory of law at all, Tamanaha may find himself closer to the essentialists whom he criticizes than he suspects, and the focus of this commentary is to explain why this may be so, and why searching for a theory of law, whether realistic or not, may be more the problem than it is the solution.
Keywords: Legal theory; Anti-essentialism; Jurisprudence; H.L.A. Hart; Legal positivism; Brian Tamanaha; Analytical jurisprudence